(untitled) (Journal of Applied Oral Science, 2017)
Research on cancer stem cells (CSCs) has greatly increased in the field of medicine and pathology; however, some conceptual misunderstandings are still present among the public as well as within the general scientific community that is not yet familiar with the subject. The very first problem is the misinterpretation of CSCs as a synonym of their normal counterparts, the well-known stem cells (SCs). Particularly in Dentistry, another common mistake is the misinterpretation of oral CSCs as normal tooth-derived SCs. The present review aims to clarify important concepts related to normal SCs and CSCs, as well as discuss the relevance of CSCs to the development, metastasis and therapy resistance of oral squamous cell carcinoma.